2017
DOI: 10.1097/phm.0000000000000810
|View full text |Cite
|
Sign up to set email alerts
|

Slow Versus Fast Robot-Assisted Locomotor Training After Severe Stroke

Abstract: In initial stages of robot-assisted locomotor training on a bodyweight-supported treadmill after severe stroke, slow training targeting discrete movement may yield greater benefit than fast training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 54 publications
2
36
0
Order By: Relevance
“…Advanced gait trainers are able to provide training with high speeds over longer periods of time, and high speeds are preferred to increase activity of the leg muscles [26,47]. Conversely, one study also found that slower training speeds may lead to greater benefits than fast training in severely affected patients early after a stroke [48].…”
Section: Locomotor Training (Lt) Principlesmentioning
confidence: 99%
“…Advanced gait trainers are able to provide training with high speeds over longer periods of time, and high speeds are preferred to increase activity of the leg muscles [26,47]. Conversely, one study also found that slower training speeds may lead to greater benefits than fast training in severely affected patients early after a stroke [48].…”
Section: Locomotor Training (Lt) Principlesmentioning
confidence: 99%
“…After removing duplicates and screening titles and abstracts, 1083 full text articles were assessed for eligibility. Twenty-eight studies were included in the systematic review 42–73. Two thousand six-hundred and seventy-seven participants were recruited to these studies—mean participant age was 72.7 years, 49.3% were males and 87% of patients sustained a cerebral infarction.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies were completed in the acute to early subacute phase poststroke,44–46 48 49 51–55 five studies were completed in the acute to late subacute phase poststroke59 62 66 68 69 and two studies were completed in the chronic phase poststroke 70 72. The most frequently used outcome measures of sensorimotor function were the Fugl-Meyer Assessment, used in 11 studies,45 46 48 51 53 54 59 68–70 72 and the MRC (Medical Research Council) scale for muscle strength, used in five studies. 46 51 52 59 72…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations